2012
DOI: 10.1111/j.1754-9485.2012.02374.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological grade of differentiation of hepatocellular carcinoma: Comparison of the efficacy of diffusion‐weighted MRI with T2‐weighted imaging and angiography‐assisted CT

Abstract: DWI was useful for evaluating the histological grade of differentiation of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 33 publications
0
20
0
1
Order By: Relevance
“…20,21 After this, few studies 23,24 were done to differentiate between benign and malignant hepatic lesions and also to differentiate between various grades of HCC. Nasu et al, 19 Piana et al, 15 and Saito et al 25 showed that there exists no relationship between ADC values and histopathological grades of HCC, whereas Heo et al 26 and Nishie et al 27 said that the ADC values of HCC had an inverse correlation with the degree of differentiation. In the present study, even though there was a decreasing trend of ADC values with increasing grade of tumor, however the decreasing trend was not statistically significant (P value of 0.118).…”
Section: Role Of Diffusion Weighted Imaging For Hepatocellular Carcinmentioning
confidence: 99%
“…20,21 After this, few studies 23,24 were done to differentiate between benign and malignant hepatic lesions and also to differentiate between various grades of HCC. Nasu et al, 19 Piana et al, 15 and Saito et al 25 showed that there exists no relationship between ADC values and histopathological grades of HCC, whereas Heo et al 26 and Nishie et al 27 said that the ADC values of HCC had an inverse correlation with the degree of differentiation. In the present study, even though there was a decreasing trend of ADC values with increasing grade of tumor, however the decreasing trend was not statistically significant (P value of 0.118).…”
Section: Role Of Diffusion Weighted Imaging For Hepatocellular Carcinmentioning
confidence: 99%
“…Details on the main published studies regarding ADC measurement and correlations with the pathological grade of HCCs are reported in Table 1. Overall, literature data show that HCC dedifferentiation tends to be associated with a decrease of the ADC value, despite differences between studies [23][24][25][26][27][28][29] . Apart from the direct correlation with the pathological grade, Nakanishi et al [29] found that ADC quantification might have a clinical prognostic value, being significantly lower in patients with early recurrence after surgery than in those without early recurrence.…”
Section: Primary Liver Tumorsmentioning
confidence: 97%
“…Arterial blood supply tends to increase during hepatocarcinogenesis. Perfusion imaging techniques [24] 99 0, 500 1.29 (WD); 1.22 (MD); 1.21 (PD) Saito et al [25] 32 100, 800 1.25 (WD); 1.12 (MD); 1.13 (PD) Muhi et al [26] 73 500, 800 0.91 (WD); 0.71 (MD); 0.68 (PD) Nishie et al [27] 80 0, 500, 1000 1.21 (WD); 1.14 (MD); 0.76 (PD) Heo et al [28] 27 0, 1000 1.20 (WD); 1.10 (MD); 0.90 (PD) Nakanishi et al [29] 44 0, 50, 1000 might provide more structural limitations than fibrosis alone. Legrand et al [44] reported that mean ADC values did not significantly differ between tumors having < 50% and those having > 50% of fibrotic stroma, or between tumors containing dense fibrosis and those containing loose fibrosis.…”
Section: Pancreatic Tumorsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21] In a study of qualitative and visual assessment using DW imaging, dynamic and hepatobiliary phase had limitations for predicting the histological grade, despite combining all these findings. 22 However, previous studies have shown that quantitative assessments including the apparent diffusion coefficient (ADC), lesion-to-liver contrast-to-noise ratio (CNR), and relative intensity ratio on hepatobiliary and arterial phase imaging seemed feasible for predicting HCC grade, 13,14,[16][17][18][19]21,23 but the clinical application of these parameters remains controversial.Recently, quantitative assessments of DW imaging using the lesion-to-liver CNR and relative contrast ratio (RCR) were shown to be superior to the ADC for predicting HCC histological grade. 16,23 However, these studies had the limitation that diagnostic accuracy was not sufficiently revealed in discriminating pHCCs from other HCCs.…”
mentioning
confidence: 98%
“…11,12 Moreover, diffusion-weighted (DW) MRI and hepatobiliary phase T1W imaging with gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd-EOB-DTPA) have been used to predict HCC grade in several studies. [13][14][15][16][17][18][19][20][21] In a study of qualitative and visual assessment using DW imaging, dynamic and hepatobiliary phase had limitations for predicting the histological grade, despite combining all these findings. 22 However, previous studies have shown that quantitative assessments including the apparent diffusion coefficient (ADC), lesion-to-liver contrast-to-noise ratio (CNR), and relative intensity ratio on hepatobiliary and arterial phase imaging seemed feasible for predicting HCC grade, 13,14,[16][17][18][19]21,23 but the clinical application of these parameters remains controversial.…”
mentioning
confidence: 98%